2004
DOI: 10.1002/ajmg.a.20668
|View full text |Cite
|
Sign up to set email alerts
|

Choanal atresia associated with prenatal methimazole exposure: Three new patients

Abstract: We report three patients with bilateral choanal atresia in children prenatally exposed to methimazole (MMI) in order to define a MMI embryopathy clinical pattern. The combination of choanal atresia and other specific malformations strongly resembles previously reported patients exposed to MMI in utero. At present, propylthiouracil is considered the best treatment in pregnancies. However in Argentina and some other countries MMI is the only antithyroid drug, possibly posing a significant risk to the unborn fetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 20 publications
(24 reference statements)
1
29
0
Order By: Relevance
“…Several case reports suggested a possible relationship between prenatal exposure to MMI and choanal atresia [Greenberg, 1987;Hall, 1997;Johnsson et al, 1997;Wilson et al, 1998;Clementi et al, 1999; Gianantonio et al, 2001;Barwell et al, 2002;Ferraris et al, 2003;Barbero et al, 2004;Foulds et al, 2005;Myers and Reardon, 2005;Ozgen et al, 2006;Wolf et al, 2006]. However, two previous epidemiological studies have not found a significant association [Momotani et al, 1984;Di Gianantonio et al, 2001].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several case reports suggested a possible relationship between prenatal exposure to MMI and choanal atresia [Greenberg, 1987;Hall, 1997;Johnsson et al, 1997;Wilson et al, 1998;Clementi et al, 1999; Gianantonio et al, 2001;Barwell et al, 2002;Ferraris et al, 2003;Barbero et al, 2004;Foulds et al, 2005;Myers and Reardon, 2005;Ozgen et al, 2006;Wolf et al, 2006]. However, two previous epidemiological studies have not found a significant association [Momotani et al, 1984;Di Gianantonio et al, 2001].…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, the finding of thyroid nuclear receptors partially occupied by T3 in fetal brain tissue at the first trimester of gestation suggests a role of thyroid hormones at an early period of the embryogenesis [Iskaros et al, Patients 1, 2, and 3 were reported previously [Barbero et al, 2004].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Reports by Greenberg [1987], Wilson et al [1998], and Barbero et al [2004] have provided strong evidence that choanal atresia is a relatively frequent feature. Lessfrequent malformations include aplasia cutis congenita [Mujtaba and Burrow, 1975;Milham, 1985], esophageal malformations [Ramirez et al, 1992;Karlsson et al, 2002], nipple anomalies [Greenberg, 1987;Wilson et al, 1998], cardiovascular defects [Sugrue and Drury, 1980;Johnsson et al, 1997] and a persistent vitelline duct [Milham, 1985].…”
Section: To the Editormentioning
confidence: 95%
“…Other wellknown syndromes having choanal atresia as a component are Crouzon syndrome, pfeiffars syndrome and treacher-colin syndrome. Alcohol, retinoic acid, methimazole, propranolol and antithyroid medication use, is thought to contribute to occurrence of choanal atresia by influencing neural crest cell migration [5] . The malformation may either be a bony plate or soft membranous tissue due to failed re-canalization of nasal fossae during fetal development.…”
Section: Introductionmentioning
confidence: 99%